The SEHATINA.ID: A Mental HealthCounseling Application to Overcome the Psychological Problems of Muslim Youth Based on a Religious Approach.(Health) - Hafiz Rafi Uddin; Khoirul Anam; Muhammad Ma’ruf Siddiqd (Faculty of Law, Universitas Negeri Semarang, 2025)
The younger generation today faces various pressures due to significant social changes, including demands from family, education, and society. Thesepressures impact their mental health, as reflected in the high number ofIndonesian adolescents experiencing mental health issues. For Muslim youth,these challenges are more complex as they must balance religious values with the pressures of modern life. Studies indicate that counseling servicescombining psychological and religious approaches are highly needed byMuslim youth. To address this need, the SEHATINA.ID platform has beendeveloped an application that integrates Islamic values with psychologicalapproaches to support holistic mental recovery. Counseling based on Islamicvalues is considered more effective as it aligns with the beliefs and needs ofMuslim youth, as emphasized in the Quran, which highlights the importanceof balancing spiritual and psychological well-being.